2021
DOI: 10.1016/j.antiviral.2021.105089
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal and antiviral activity of astodrimer sodium against SARS-CoV-2 in vitro

Abstract: An effective response to the ongoing coronavirus disease (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) will involve a range of complementary preventive modalities. The current studies were conducted to evaluate the in vitro SARS-CoV-2 antiviral and virucidal (irreversible) activity of astodrimer sodium, a dendrimer with broad spectrum antimicrobial activity, including against enveloped viruses in in vitro and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…[58] More recently, SPL7013 demonstrated antiviral activity against SARS-CoV-2 in vitro at concentrations found in their Viraleze antiviral nasal spray. [59] In addition to heparan sulfate, sialic acid, which is found on the terminal branches of N-and O-glycans, is another well-established binding motif, [56a] with the α5-N-acetylneuramic acid (Neu5AC) form recognized as the preferred attachment point for influenza A and B viruses. [60] Sialic acid has also been identified as a binding target of coronavirus spike proteins.…”
Section: Synthetic Antiviral Polymersmentioning
confidence: 99%
“…[58] More recently, SPL7013 demonstrated antiviral activity against SARS-CoV-2 in vitro at concentrations found in their Viraleze antiviral nasal spray. [59] In addition to heparan sulfate, sialic acid, which is found on the terminal branches of N-and O-glycans, is another well-established binding motif, [56a] with the α5-N-acetylneuramic acid (Neu5AC) form recognized as the preferred attachment point for influenza A and B viruses. [60] Sialic acid has also been identified as a binding target of coronavirus spike proteins.…”
Section: Synthetic Antiviral Polymersmentioning
confidence: 99%
“…The single exposure of the virus to astodrimer sodium 1% nasal spray formulation for 60 min in the virucidal study (Group 3.2) did not result in the absence of the virus detected in nasal secretions but did result in a lack of viraemia compared to the PBS control (Group 3.1). In vitro virucidal studies by our group demonstrated a reduction in viral titre of up to 99.99% when 1% astodrimer sodium was used to block SARS-CoV-2 (USA-WA1/2020) infection [ 2 ]. Whilst the current virucidal in vivo study demonstrates partial protection from exposure to 3 × 10 2 PFU SARS-CoV-2 (USA-WA1/2020), the results suggest at least one virus escaped and established a very low-grade infection.…”
Section: Resultsmentioning
confidence: 99%
“…The quantitation of the infectious virus in the tissue homogenates was performed by plaque assay, as described in Paull et al, 2021 [ 2 ], with Vero E6 cells as the detecting cell line.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecule has now shown activity against newly discovered variants of concern including the Alpha or UK (B.1.1.7) and the more recent Delta SARS-CoV-2 variant [159]. A recent article by Paull et al found that astodrimer sodium (SPL7013) can inhibit the replication of SARS-CoV-2 in vivo, and such irreversibly blocked interaction leads SARS-CoV-2 to no longer infect cells [160]. Starpharma also announced the release of a nasal spray [161] under the tradename VIRALEZE™ as a promising weapon against COVID-19 that will aid in filling the gap during challenging global vaccine rollouts [162].…”
Section: Peptide Multimers As Antimicrobial and Antiviral Agentsmentioning
confidence: 99%